2014
DOI: 10.1002/wcs.1334
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor Val66Met polymorphism, human memory, and synaptic neuroplasticity

Abstract: Some people have much better memory than others, and there is compelling evidence that a considerable proportion of this variation in memory ability is genetically inherited. A form of synaptic plasticity known as long-term potentiation (LTP) is the principal candidate mechanism underlying memory formation in neural circuits, and it might be expected, therefore, that a genetic influence on the degree of LTP might in turn influence memory abilities. Of the genetic variations thought to significantly influence m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 106 publications
0
28
0
1
Order By: Relevance
“…One of those factors can be genetic variation. Such a genetic variation is the presence of a single-nucleotide polymorphism of the BDNF Val66Met gene, which may detrimentally influence the capacity of learning (Lamb et al 2015). In our previous work we found that post stroke subjects who are BDNF Val66Met carriers (MET) require more time to learn split-belt treadmill walking in a single session (i.e.…”
Section: Effect Of Exercise On Learning May Be Context Specificmentioning
confidence: 99%
“…One of those factors can be genetic variation. Such a genetic variation is the presence of a single-nucleotide polymorphism of the BDNF Val66Met gene, which may detrimentally influence the capacity of learning (Lamb et al 2015). In our previous work we found that post stroke subjects who are BDNF Val66Met carriers (MET) require more time to learn split-belt treadmill walking in a single session (i.e.…”
Section: Effect Of Exercise On Learning May Be Context Specificmentioning
confidence: 99%
“…The BDNF Val66Met polymorphism is understood to impact the efficacy of NMDARdependent plasticity (Chen et al, 2004;Egan et al, 2003;Lamb et al, 2015), which is central to both the generation of the MMN Schmidt et al, would thus be reasonable to predict a comparable genetic group difference across both paradigms. However, genetic differences were only apparent in the modulation of backward connections for the MMN paradigm, with no significant genetic differences observed in the LTP generative network.…”
Section: Hebbian Ltp and Predictive Codingmentioning
confidence: 99%
“…Approximately 25-50% of the population carry the rs6265 single nucleotide polymorphism (SNP) (4-16% homozygous) which substitutes valine to methionine at codon 66 (known as Val66Met) (Goldberg & Weinberger, 2004;Shimizu, Hashimoto, & Iyo, 2004). The Met allele of the SNP is associated with reduced secretion of BDNF, and thus has previously been implicated in the efficacy of NMDAR-dependent neuroplasticity and memory performance (Chen et al, 2004;Egan et al, 2003;Hariri et al, 2003;Lamb et al, 2015). Previous studies conducted in our lab using the LTP paradigm have demonstrated reduced potentiation of the N1b component of the VEP in BDNF Met carriers (Thompson et al, in prep).…”
mentioning
confidence: 99%
“…Brain derived neurotrophic factor (BDNF) is one of the most abundant neurotrophins in the brain, associated with synaptic plasticity and necessary in the mature brain to maintain dendritic density and structural integrity of neurons (Hofer et al, 1990;Wetmore et al, 1990;Ghosh et al, 1994;Murer et al, 2001;Lamb et al, 2014). The BDNF Val 66 Met polymorphism (rs6265), where adenosine (A) is substituted for guanine (G) at codon 66 leading to the valine (Val) being substituted by methionine (Met), is associated with less BDNF secretion and differences in brain function and structure (Pezawas et al, 2004;Lamb et al, 2014).…”
Section: Brain Derived Neurotrophic Factor Val 66 Met Polymorphismmentioning
confidence: 99%
“…Brain derived neurotrophic factor (BDNF) is one of the most abundant neurotrophins in the brain, associated with synaptic plasticity and necessary in the mature brain to maintain dendritic density and structural integrity of neurons (Hofer et al, 1990;Wetmore et al, 1990;Ghosh et al, 1994;Murer et al, 2001;Lamb et al, 2014). The BDNF Val 66 Met polymorphism (rs6265), where adenosine (A) is substituted for guanine (G) at codon 66 leading to the valine (Val) being substituted by methionine (Met), is associated with less BDNF secretion and differences in brain function and structure (Pezawas et al, 2004;Lamb et al, 2014). It has been shown that Met allele carriers have a reduced cortical thickness in the frontal lobe and ACC compared to Val allele carriers, and that the difference is more drastic in those diagnosed with MDD (Legge et al, 2015) The presence of a Met allele is associated with an increased risk for developing depression, although this finding is inconsistent (Egan et al, 2003;Verhagen et al, 2010).…”
Section: Brain Derived Neurotrophic Factor Val 66 Met Polymorphismmentioning
confidence: 99%